2020
DOI: 10.1111/ejh.13377
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 study of ibrutinib in combination with bortezomib and dexamethasone in patients with relapsed/refractory multiple myeloma

Abstract: Objective:We evaluated ibrutinib, a once-daily inhibitor of Bruton's tyrosine kinase, combined with bortezomib and dexamethasone in patients with relapsed or relapsed/ refractory multiple myeloma who had received 1-3 prior therapies. Methods:This was a phase 2, single-arm, open-label, multicentre study (NCT02902965).The primary endpoint was progression-free survival (PFS). Results:Seventy-six patients were enrolled; 74 received ≥1 dose of study treatment. After median follow-up of 19.6 months, median PFS was 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Infectious complications were reported in 92% (44/48) of trials with sufficient data for the final analysis. Table and Table summarize findings for those studies investigating ibrutinib as a single agent, or in combination with one or more other antineoplastics, respectively. One single‐agent trial and 3 combination studies included in the final infectious AE data had no reported infectious complications.…”
Section: Resultsmentioning
confidence: 99%
“…Infectious complications were reported in 92% (44/48) of trials with sufficient data for the final analysis. Table and Table summarize findings for those studies investigating ibrutinib as a single agent, or in combination with one or more other antineoplastics, respectively. One single‐agent trial and 3 combination studies included in the final infectious AE data had no reported infectious complications.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, 57% of patients had clinical responses with a median response duration of 9.5 months. The study was ultimately terminated due to an inability to achieve the primary endpoint [ 67 ].…”
Section: How Good a Target Is Btk For Myeloma Therapy?mentioning
confidence: 99%
“…[74] Ibrutinib has failed to show any major benefit in relapsed myeloma and follicular lymphoma. [75,76] The drug modulates the tumor microenvironment and hence, it has been tried with some success in varied nonhematological malignancies including gynecological malignancies, pancreatic carcinoma, prostate cancer, and glioblastoma multiforme. [77][78][79][80]…”
Section: Other Malignanciesmentioning
confidence: 99%